PENGARUH PENERAPAN MODEL COOPERATIVE LEARNING TIPE NUMBER HEAD TOGETHER (NHT) TERHADAP SIKAP KERJA SAMA SISWA KELAS V SD NEGERI BEROANGING KOTA MAKASSAR - Widya Karmila Sari Achmad; Andi Makkasau; Annisa Nurul Magfira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This quasi-experimental study aims to determine the effect of applying the Cooperative Learning Model Type Numbered Heads Together (NHT) on the cooperative attitude of fifth-grade students at SD Negeri Beroanging, Makassar City. The independent variable in this study is the NHT learning model, while the dependent variable is students’ cooperative attitude. The study involved two classes, with 15 students from class VA as the experimental group and 15 students from class VB as the control group. Data were collected through pre-test and post-test questionnaires and analyzed using descriptive and inferential statistical methods. The results showed that the implementation of the NHT model was carried out very well and significantly improved students’ cooperative attitudes. The N-gain score of the experimental group was higher than that of the control group, indicating that the NHT model had a positive effect on students’ cooperation skills.